The Burden of Non-Motor Symptoms in Parkinson’s Disease: A Cross-Sectional Study on Clinical Correlates and Quality of Life in Quetta, Pakistan - Kakar, Amanullah; Kakar, Ainullah; Ahmed, Riaz; Qahir, Muhammad; Nasar, Abdul Bari; Ihsan ul Haq; Essa, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Parkinson’s disease (PD) patients’ quality of life (QoL) is greatly impacted by non-motor symptoms (NMS), however, there is still a lack of a thorough definition of these symptoms in varied regional populations like Pakistan. This study aimed to delineate non-motor symptoms (NMS), their correlations with clinical characteristics, and their influence on quality of life (QoL) in a cohort of Parkinson’s disease (PD) patients from Quetta, Pakistan. Methods: This cross-sectional study encompassed 86 Parkinson’s disease patients prospectively recruited from the Neurology Outpatient Department of Bolan Medical Complex Hospital in Quetta. Demographic data, disease features, quality of life (PDQ-39, Schwab & England ADL), and biomarkers were gathered. Statistical analyses encompassed descriptive statistics, bivariate analyses, and multivariate analyses (linear and logistic regression). Results: The study population exhibited a mean age of 64.3±9.1 years, with a male predominance of 67.4%. A significant prevalence of NMS was noted, encompassing cognitive impairment (mean MoCA: 21.8±3.9), severe depression (23.3), and sleep problems (median PDSS-2: 20). Quality of life was markedly diminished (median PDQ-39: 48). Prolonged disease duration (rho = 0.45, p<0.001) and advanced H&Y stage (H = 18.2, p=0.001) were predictive with increased NMS burden. Conclusion: Non-motor symptoms are exceedingly frequent and substantially affect the quality of life in Parkinson’s disease patients from Quetta, Pakistan. The advancement of disease and depression are significant indicators of NMS burden. These findings underscore the essential requirement for regular NMS screening and comprehensive care strategies to enhance patient outcomes in this marginalized community.